Mesenchymal stem cells for treatment of musculoskeletal disease in horses: Relative merits of allogeneic versus autologous stem cells. (19th February 2020) - Colbath, Aimée C.; Dow, Steven W.; McIlwraith, C. Wayne; Goodrich, Laurie R.
Abstract: Mesenchymal stem cells (MSCs) are widely used for treatment of musculoskeletal diseases in horses, but there is ongoing debate regarding the relative safety and efficacy of allogeneic MSCs, compared with autologous equine MSCs. This review summarises the currently available published data regarding the therapeutic use of autologous and allogeneic MSCs in horses. Arguments that have been advanced against the use of allogeneic MSCs include higher risk of immunological reactions and shorter cell survival times following injection. Arguments favouring the use of allogeneic MSCs include the ability to bank cells and reduce the time to treatment, to collect MSCs from younger donor animals and the ability to manipulate banked cells prior to administration. In vitro studies and a limited set of experimental in vivo studies have indicated that adverse immunological reactions may occur when allogeneic MSCs are administered to horses. However, newer studies lack evidence of inflammatory reactions or adverse clinical responses when allogeneic MSCs are administered and compared with autologous MSCs. Thus, while the relative merits of allogeneic vs autologous MSCs for treatment of musculoskeletal injuries in horses have not been fully established, accumulating evidence from studies in horses suggests that allogeneic MSCs maybe a safe alternative to autologous MSCs. Large, properly designed, randomised trials in addition to careful immunological evaluation of short‐term and long‐term, local and systemic immune responses are needed to more fully resolve the issue.